IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DENGAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 2 BANYUURIP TEMANGGUNG - Ridiyanto, Ridiyanto; Daimul Hasanah; Heri Maria Zulfiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the planning, implementation and evaluation of differentiated learning using the Problem Based Learning model and the obstacles and solutions in learning material in the form of objects and their changes in science and science learning for grade IV elementary schools. This research uses a descriptive qualitative approach. Data was obtained by observation, interviews and documentation. This research began with an analysis of student needs, including mapping learning needs based on three aspects, namely learning readiness, learning interest, and student learning profile. Second, plan learning as outlined in differentiated teaching modules based on mapping results, namely providing various choices of strategies, materials and ways of learning. The differentiation learning strategy used includes content and process differentiation. The next step is to evaluate and reflect on the learning that has taken place, this is used to improve future learning. Differentiated learning using the Problem Based Learning model on material forms of objects and changes carried out in class 4 of SD Negeri 2 Banyuurip, Temanggung is very effective, this can be seen from the activeness of students in participating in learning, apart from that the increase in student learning outcomes has also increased. However, they also encounter obstacles such as requiring a lot of time, limited resources, and teachers' skills in managing the class. To overcome this, the teacher and the principal hold learning reflections to improve so that further learning becomes more effective.